Non-local boundary value problem for partial differential equation in a complex domain - Il'kiv, V.S.; Volyans'ka, I.I. (Carpathian Mathematical Publications, 2014)
The paper is devoted to the investigation of a non-local boundary value problem for partial differential equations with the operator of the generalized differentiation B=zz, which operate on functions of scalar complex variable z. The unity theorem and existence theorems of the solution of problem in the space H_q^n(D) are proved. Correctness after Hadamard of the problem is shown. It distinguishes her from an ill-conditioned after Hadamard problem with many spatial variables.